Generation of supercontinuum via femtosecond pulse propagation in a highly nonlinear photonic crystal fiber - Gabayno, Jacque Lynn Ferranco (2005)
A supercontinuum spanning the near infrared to the visible spectral region is generated in a 73 cm. long highly nonlinear photonic crystal fiber (2.3nm core diameter, zero-dispersion wavelength at 790nm) using a wavelength-tunable mode-locked femtosecond T1: Sapphire laser (52fs pulse width at 790nm and 82MHz and 82MHz repetition rate) The evolution of the fermotosecond pulses into a broadband continuum is investigated for different pump wavelength and input power. Spectral brosdening is highly sensitive to the input power. Measured spectral linewidths increases with increasing excitation intensity. Maximum broadening of 380nm, 388nm aqre measured for pump wavelength centered at 788nm, 794nm, and 804nm, respectively.A complex interplay of different nonlinear effects such as four-wave mixing, self-phase modulation, stimulated Raman scattering, and soliton-self-frequency shift have significant roles in the generation of the supercontinuum. In the normal dispersion region for a pump wavelength at 788nm, higher order dispersion effects broaden the pulse at low pump power. Soliton self-frequency shift, stimulated Raman scattering, and four-wave mixing are the predominant mechanisms in the generation of a supercontinuum for high input intensity. In the anomalous dispersion region for pump wavelengths at 794nm and 804nm, self-phase modulation assists in the frequency shifting towards shorter wavelengths at very low input power. At high excitation intensity, spectral broadening is enhanced by four-wave mixing and stimulated Raman scattering. Excitation intensity and pump wavelength is obeserved to affect the temporal coherence property of the generated supercontinuum. Depending on the application of the broadband spectrum, the temporal coherence length can be tuned by varying the excitation power and input wavelength.
"April 2005."
Vitae.
Thesis (M.S. Physics)--University of the Philippines Diliman.
Keywords: Optical fibers; Photonic crystals; Femtochemistry; Laser pulses, Ultrashort